STRATEGI PEMASARAN JASA PENDIDIKAN DALAM MENINGKATKAN DAYA SAING LEMBAGA: STUDI KASUS MTsN 15 BOYOLALI - Mana Sikana, Arina; Ibrahim, Rustam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the marketing strategy of educational services at MTsN 15 Boyolali based on the 7P marketing mix and to identify the supporting and inhibiting factors. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with the principal and the public relations vice principal, participant observation, and documentation (brochures, flyers, social media, activity photos). The findings indicate that MTsN 15 Boyolali has implemented the 7P strategy reasonably well. The main strengths include the product (extracurricular activities such as drum band, hadroh, dance, tilawah, futsal, volleyball, scouting, table tennis, and national achievements), flexible pricing policies (fee reductions for outstanding students, discounts for twins/siblings, and health assistance), integrated promotion (all social media, flyers, posters, outreach to elementary schools, and an academic ability test for elementary school students with the top 35 ranks automatically accepted), and physical evidence (new building, mosque, sports field). The supporting factors are the principal's commitment, the enthusiasm of targeted schools, and the attractiveness of extracurricular activities and the new building. The inhibiting factor is competition with established senior schools nearby. The madrasah has been able to maintain its competitiveness with enrollment figures meeting the targets. Recommendations include strengthening digital promotion and consistently highlighting achievements and extracurricular activities.